2014
DOI: 10.1158/1535-7163.mct-13-0729
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Inhibitor of DNA Topoisomerase I, Camptothecin, Modulates HIF-1α Activity by Changing miR Expression Patterns in Human Cancer Cells

Abstract: DNA topoisomerase I (Top1) inhibition by camptothecin derivatives can impair the hypoxia-induced cell transcriptional response. In the present work, we determined molecular aspects of the mechanism of camptothecin's effects on hypoxia-inducible factor-1a (HIF-1a) activity in human cancer cells. In particular, we provide evidence that low concentrations of camptothecin, without interfering with HIF-1a mRNA levels, can reduce HIF-1a protein expression and activity. As luciferase assays demonstrated the involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 42 publications
0
40
0
1
Order By: Relevance
“…However, the activity and regulatory mechanisms of miR-18a are not fixed across various pathological and physiological conditions, or in different types of tumors, and factors that are associated with invasive meningiomas are not limited to HIF-1α (23)(24)(25). In addition, there are abundant miRNAs that may potentially regulate these factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the activity and regulatory mechanisms of miR-18a are not fixed across various pathological and physiological conditions, or in different types of tumors, and factors that are associated with invasive meningiomas are not limited to HIF-1α (23)(24)(25). In addition, there are abundant miRNAs that may potentially regulate these factors.…”
Section: Discussionmentioning
confidence: 99%
“…It also can induce p53-dependent DNA damage in renal cell carcinoma (8). In another report, camptothecin induces apoptosis through the hypoxia-inducible factor-1α (HIF-1α) pathway in HeLa (human cervix adenocarcinoma cell line) (9). In the HCT116 coloretctal cancer cell, camptothecin can induce apoptosis through the AMPK-TSC2-mTOR pathway (10).…”
Section: Diterpenoidmentioning
confidence: 99%
“…Mechanistically it was reported that camptothecin exerted its inhibitory effects via upregulating expression of miR-155 (Bertozzi et al, 2014).…”
Section: Mir-155: In Vitro Studiesmentioning
confidence: 99%